Review on the Impact of Milk Oligosaccharides on the Brain and Neurocognitive Development in Early Life - Fan, Yuting; McMath, Arden L.; Donovan, Sharon M. (Nutrients, 2023)
Milk Oligosaccharides (MOS), a group of complex carbohydrates found in human and bovine milk, have emerged as potential modulators of optimal brain development for early life. This review provides a comprehensive investigation of the impact of milk oligosaccharides on brain and neurocognitive development of early life by synthesizing current literature from preclinical models and human observational studies. The literature search was conducted in the PubMed search engine, and the inclusion eligibility was evaluated by three reviewers. Overall, we identified 26 articles for analysis. While the literature supports the crucial roles of fucosylated and sialylated milk oligosaccharides in learning, memory, executive functioning, and brain structural development, limitations were identified. In preclinical models, the supplementation of only the most abundant MOS might overlook the complexity of naturally occurring MOS compositions. Similarly, accurately quantifying MOS intake in human studies is challenging due to potential confounding effects such as formula feeding. Mechanistically, MOS is thought to impact neurodevelopment through modulation of the microbiota and enhancement of neuronal signaling. However, further advancement in our understanding necessitates clinical randomized-controlled trials to elucidate the specific mechanisms and long-term implications of milk oligosaccharides exposure. Understanding the interplay between milk oligosaccharides and cognition may contribute to early nutrition strategies for optimal cognitive outcomes in children.